Work and sexual diversity. Transgressive narratives against the concept of «Decent Work» - Álvarez, Roland (2019)
The present paper is an adaptation of the research paper presented to the Erasmus University Rotterdam for obtaining the degree of Master of Arts in Development Studies. In 2011, I considered that «the concept of decent work is a tool that seeks to extend rights and protection to workers. However, what happens in the case of Peruvian transvestite migrant sex workers? Based on the fact of the type of work they do, what perceptions and meanings are built on non-discrimination in work and social security, components of decent work?» (Alvarez, 2011, p. 1). This research seeks to investigate those meanings that are constructed by transvestite from their daily life and with reference to certain socioeconomic conditions, as well as to delve a little deeper into the personal and social reasons underlying these meanings.